A sub-supersolution approach for Neumann boundary value problems with gradient dependence. (August 2020) - Motreanu, Dumitru; Sciammetta, Angela; Tornatore, Elisabetta
Abstract: Existence and location of solutions to a Neumann problem driven by an nonhomogeneous differential operator and with gradient dependence are established developing a non-variational approach based on an adequate method of sub-supersolution. The abstract theorem is applied to prove the existence of finitely many positive solutions or even infinitely many positive solutions for a class of Neumann problems.